Effectiveness of a Structured Teaching Programme on Knowledge Regarding Organ Donation among Undergraduate Nursing Students: A Quasi-Experimental Study - Suhasini Christian, Dr. Ravindra HN, Dr. Swapnil V. Rahane (Journal of Daoist Studies, 2026)
Background: Organ donation remains one of the most effective means to save the lives of people with end-stage organ failure. However, a lack of information among healthcare professionals and students remains a key barrier to the promotion of organ donation. As future health care workers, nursing students play a significant role in raising awareness and encouraging the public to become organ donors. Hence, educational interventions are crucial to improve their knowledge and readiness. Objective: To assess the effectiveness of an organised training programme on knowledge related organ donation among undergraduate nursing students. Methods: A quantitative study was conducted using a quasi-experimental one-group pre-test post-test design on 325 undergraduate nursing students recruited by multistage sampling process from nursing colleges affiliated to Gujarat University, Ahmedabad. Baseline knowledge was measured with a validated structured knowledge questionnaire comprising 30 items. Participants then underwent a comprehensive teaching curriculum on organ donation. The post-test was performed using the same questionnaire two weeks after the intervention. IBM SPSS Statistics version 29.0 was used to analyse data. Descriptive statistics were utilized to summarize participant characteristics and the paired-samples t-test was employed to test the efficiency of the intervention. Results: Before the intervention, 60.0% of the participants had inadequate knowledge, 26.2% had moderate knowledge and 13.8% had adequate knowledge. Post-intervention, the proportion of participants with adequate knowledge increased to 47.7%, while the proportion with inadequate knowledge decreased to 24.3%. The mean knowledge score improved considerably from 6.42 ± 2.12 in pre-test to 9.84 ± 2.62 in post-test (t = 18.622, df = 324, p < 0.001). It shows the effectiveness of a structured training programme. Conclusion: A structured education plan has a considerable impact on the knowledge of nursing students regarding organ donation. Implementing educational interventions on organ donation in undergraduate nursing curriculum may enhance future nurses’ ability to educate patients, advocate for organ donation, and contribute to improving organ donation practices.